The Impact of Islam on Arab Thought - Hammadi, Hammad Farhan; Indo Santalia; Abdullah; Muhsin (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2024)
The Arabs before Islam had an advanced civilization, such as the Mesopotamian Civilization in Iraq and the Nile Valley Civilization in Egypt. Additionally, there were kingdoms in the Arabian Peninsula and the Levant. They possessed qualities that prepared them to receive and convey the divine message, as Allah says: You are the best nation produced [as an example] for mankind (Ali Imran: 110). However, Allah also described some of their behaviors as